Comparative Cross-Market Research of ICT Industry Impact on World Goods Markets: a Quantitative Research - Tetiana MELNYK; Andrii OLIINYK; Maryna SLOKVA; Olga GONCHAROVA; Ihor CHORNODID; Оlena KRAVCHENKO (Communications of International Proceedings, 2023)
The rapid advancement of information and communications technology (ICT) has had a transformative impact on global markets. This article presents a comparative cross-market research study aimed at understanding the influence of the ICT industry on global goods markets, encompassing both advanced and developing economies. It analyzes the impact of ICT utilization on various goods sectors, including agricultural products, ores and metals, mineral fuels and oils, chemicals, light industry products, wood industry products, machinery and equipment, tools and devices, and other goods. The research design utilizes multiple linear regression analysis, and the data is sourced from international databases from 2005 to 2021 periods. The study considers control variables, including trade openness, consumer price index, GDP growth, GDP per capita, and political stability. The results indicate that the export and import of ICT services have both positive and negative impacts on different goods sectors export and import in advanced and developing economies due to their economic development. While ICT deployment index plays a significant role in the general growth of the goods market in both advanced and developing economies, except for agricultural products import. The study provides valuable insights into the complex and multifaceted relationship between the ICT industry and global goods markets, informing policymakers, businesses, and stakeholders about the strategic importance of ICT development and utilization in driving trade flows and competitiveness.
Keywords: ICT industry; ICT services market; world goods market; trade; GDP